Spinning Wheel dalam Pembelajaran Kosakata Bahasa Jerman - A Nurhikmatul Jannah; Abdul Kasim Achmad; Syamsu Rijal (Academic : Journal of Social and Educational Studies, 2024)
Abstract. This study aims to find out the improvement of the students' German vocabulary. This research is a classroom action research consisting of two cycles to find out the planning, process, and results of the Spinning Wheel game in improving the German vocabulary of class X UPT SMA Negeri 12 Bulukumba. This type of research is a descriptive qualitative method. The subjects in this study were students of class X MIPA 2 UPT SMA Negeri 12 Bulukumba consisting of 27 students. The results of this study indicate that the percentage values obtained by students in cycle I reached 93% and cycle II reached 96%. These results indicated that the Spinning Wheel game can improve the German vocabulary of class X UPT SMA Negeri 12 Bulukumba.Keywords: Vocabulary, Improvement, German, Spinning Wheel